DEVELOPMENT OF AUGMENTED REALITY MEDIA TECHNOLOGY ANDOID-BASED APPLICATIONS ON LEARNING “CULTURAL DIVERSITY IN INDONESIA” ELEMENTARY SCHOOL - Geby Angelina Nainggolan; Nurnidah Hanifah; Rana Gustian Nugraha (Universitas Majalengka, 2024)
Media in social studies learning material on cultural diversity in Indonesia still only uses pictures in books as an intermediary tool for learning. This makes students quickly bored and understanding of the material received quickly forgotten by students due to the lack of visualization channeled on the concept of material. This study aims to find out the development of android-based application media with augmented reality technology on learning cultural diversity in Indonesia. This study uses the Design and Development (D&D) development research method with the ADDIE development model (Analzye, Design, Development, Implementation, and Evaluation) with the research subject, namely class IV students totaling 24 people at one of the State Elementary Schools located in Bandung Regency, West Java. The data collection techniques used in this study are using expert validation questionnaires and response questionnaires that aim to determine the feasibility of learning media android-based applications with augmented reality technology as a learning medium in social studies learning material on cultural diversity in Indonesia. The results of the material expert validation test get a percentage of 98% and media expert validation gets a percentage of 94%. Meanwhile, the results of user response (teacher) get a percentage of 94%. In addition, the results of student responses obtained from limited trials get a percentage of 92% and broad trials get a percentage of 87%. Therefore, it can be concluded that the learning media android-based applications with augmented reality technology is very feasible to use in the social studies learning process.